2017
DOI: 10.1111/tra.12472
|View full text |Cite|
|
Sign up to set email alerts
|

Global and local mechanisms sustain axonal proteostasis of transmembrane proteins

Abstract: The control of neuronal protein homeostasis or is tightly regulated both spatially and temporally, assuring accurate and integrated responses to external or intrinsic stimuli. Local or autonomous responses in dendritic and axonal compartments are crucial to sustain function during development, physiology and in response to damage or disease. Axons are responsible for generating and propagating electrical impulses in neurons, and the establishment and maintenance of their molecular composition are subject to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 128 publications
(274 reference statements)
2
17
0
Order By: Relevance
“…In the present study, deep sequencing of polyadenylated RNA present in a single D. gigas giant axon has revealed an exhaustive list of mRNAs that encode many proteins known to be involved in protein synthesis, modification and folding (Supplementary Table S1 ). This is in agreement with transcriptome studies of the axonal electrical signaling compartment obtained from several other types of neurons, which have shown an mRNA repertoire indicative of axonal translation 30 , 33 35 , 62 , thus suggesting that local protein synthesis is likely a fundamental property of axons 1 , 2 , 58 , 63 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, deep sequencing of polyadenylated RNA present in a single D. gigas giant axon has revealed an exhaustive list of mRNAs that encode many proteins known to be involved in protein synthesis, modification and folding (Supplementary Table S1 ). This is in agreement with transcriptome studies of the axonal electrical signaling compartment obtained from several other types of neurons, which have shown an mRNA repertoire indicative of axonal translation 30 , 33 35 , 62 , thus suggesting that local protein synthesis is likely a fundamental property of axons 1 , 2 , 58 , 63 .…”
Section: Discussionsupporting
confidence: 90%
“…Much of the axonal electrical signal transmission function has been shown to be manifested at its membrane. The possibility that axons can synthesize membrane proteins locally has been under extensive investigation 1 , 2 , 58 , 59 , as it can provide new mechanistic insights for maintenance of proper axonal function. Here we have shown that the axoplasm of squid giant axon contains a transcriptome representative of a compartment with membrane protein synthesis and trafficking capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…As in all cells, neuronal trafficking of lipids and proteins from the ER to the Golgi is essential for numerous cell biological processes, and we refer readers to several excellent reviews on the functions of ER-to-Golgi transport and the broader secretory pathway in relation to neuronal function and protein trafficking (Cornejo et al, 2017;Hanus and Ehlers, 2016;Jan and Jan, 2010;Lai and Jan, 2006;Pfenninger, 2009).…”
Section: Roles Of the Secretory Pathway In Neuronsmentioning
confidence: 99%
“…Thus, tight regulation of ion channel expression within dendrites, axons and the presynaptic domain is critical for robust information transfer within the nervous system. While local translation of transported mRNAs can occur in axons and dendrites (Cornejo et al, 2017; Van Driesche and Martin, 2018), the canonical trafficking route of membranelocalised ion channels involves directed transport via post-Golgi transport vesicles to the dendritic or axonal domains (Cornejo et al, 2017;Hirokawa and Takemura, 2005), necessitating trafficking through the somatic ER and Golgi apparatus.…”
Section: Ion Channel Traffickingmentioning
confidence: 99%
“…However, the timely delivery of components may be challenging in distant neuronal compartments, especially under rapid metabolic demands during axonal development, plasticity or regeneration. Thus, the astonishing extension and complexity of axons may be supported by the local synthesis of lipids and secreted and transmembrane proteins (Alvarez et al, ; Brittis et al, ; Merianda et al, ; Cornejo et al, ).…”
Section: The Multiple Functions Of the Axonal Ermentioning
confidence: 99%